Genetic structure of longtail shad [Tenualosa macrura (Bleeker, 1852)] populations in Sarawak and phylogenetic relationships among clupeids - Ahmad Tarmizi, Nona Nabilah (2018)
The tropical shad of genus Tenualosa (subfamily Dorosomatinae) is locally known in Malaysia as ikan terubok. They are important estuarine fishes, both commercially and culturally in many Asian countries including Malaysia. However, the phylogenetic relationship of family Clupeidae and genetic information on the population structure are still poorly understood. Therefore, this study examined the phylogenetic relationships of tropical shad of genus tenualosa and their relationships with other selected clupeids using sequence analysis of mitochondrial DNA cytochrome c oxidase I (COI) gene. This study also describe the genetic structure and level of genetic diversity ofTenualosa macrurasamples, using sequence analysis of 604 base pair (bp) of the mitochondrial COI gene. A total of 51 T. macrurawere analysed from 3 locations throughout Sarawak on Batang Sadong (n = 19), Samarahan (n = 21) and Mukah (n = 11). All samples were obtained from various localities throughout the coastal areas of Sarawak, Peninsular Malaysia and Bangladesh.The sequences were analysed using BLAST, BOLD, CLUSTAL X, MEGA 6.06, DnaSP programme, Network 5.003 and Arlequin software. A total of 47 haplotypes were obtained from 132 sequences of clupeids. A total of 604bp of the COI sequences were obtained with 367bp conserved sites, 241bp variable sites and 227bp parsimony informative sites. The study proved the monophylies of the subfamiles Alosinae, Dorosomatinae and Clupeinae within the clupeids family. Between the two shads, namely, Tenualosa macrura and Tenualosa toli, high genetic divergences found between them (12.1-13.5 %) supported their taxonomic status as distinct species. In total, 7 haplotypes of Tenualosa macrurawere found, with 3singleton haplotypes and 4 haplotypes being shared among 3 populations. The experimental and statistic results of the mitochondrial COI analysis revealed that the haplotype diversity varied from 0.6257 to 0.6546 and nucleotide diversity ranged from 0.0012 to 0.0158, which pointed out that very high gene flow occur between the populations. Analysis of molecular variance (AMOVA) of Sadong, Mukah and Samarahan populations does not suggest existence of population structuring in Tenulosa macrura and suggested existence of a single population. The low level of mtDNA (2.36 %) differences currently found among Tenualosa macrura populations is probably due small number of samples used in the study.Overall, this study has managed to provide a better insight on the phylogeny, genetic identity and level of genetic differences and population structure of Tenualosa macrura and between fishes of Clupeidae.